True blue through oxidation: a thiaazulenic heterophenoquinone as electrochrome - Intorp, Sebastian; Kushida, Soh; Rominger, Frank; Freudenberg, Jan; Hinkel, Felix Peter; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
A thiaazulenic quinone TAQ was synthesized and its optical and redox properties were investigated. The deep blue-colored compound is readily and reversibly reduced to the colorless anionic state. Electrochromic films were prepared and showed reversible switching behavior for the anodically coloring and NIR electrochromic material.
Gesehen am 23.07.2019